ENDIANDRA KASSAMENSIS (LAURACEAE), A NEW SPECIES FROM NEW GUINEA - Deby Arifiani (BIOTROPIA, 2012)
A new species of Endiandra (Lauraceae) is described from New Guinea. Endiandra kassamensis is described based on specimens collected over four decades ago. Unlike most Endiandra which grow in lowland forest, E. kassamensis is found in high altitude forest. The species is characterized by the presence of staminodia with the absence of staminal glands. Â  Key words: Endiandra, Lauraceae, staminal glands, staminodia, endemic, New Guinea